Construction of Efficient Solid Emitters with Tetraphenylethene Trimers for Non‐doped Blue OLEDs. Issue 7 (July 2014) - Huang, Jing; Sun, Ning; Wang, Jinyu; Tang, Runli; Li, Xuefeng; Dong, Jingfeng; Li, Qianqian; Ma, Dongge; Li, Zhen
Abstract Three TPE trimers with meta or para linkage modes have been successfully synthesized. When fabricated as emissive layers in non‐doped OLEDs, they all exhibit blue or deep‐blue emissions with maximum current efficiency up to 4.03 cd A−1, further verifying the facile but ingenious approach by utilizing meta‐linkage mode in longer conjugated systems.